Minat Pilih Dan Gen Z: Personal Branding Prabowo Pada Pilpres 2024 Di Daerah Istimewa Yogyakarta - Vika Puja Kesuma; Latifa Zahra (Jurnal Ilmu Komunikasi, 2026)
The Presidential Election (Pilpres) is a crucial moment in Indonesia's democratic system, and in the 2024 Presidential Election, Generation Z plays a significant role as a potential voter cohort. Generation Z places a high value on personal branding when choosing a leader. Prabowo Subianto, as one of the potential candidates, builds a self-image that is more relaxed, humorous, and close to the younger generation. Therefore, this study aims to analyze the influence of Prabowo Subianto's personal branding on Generation Z voters' interest in the 2024 presidential election in the Special Region of Yogyakarta (DIY). This study uses indicators from Montoya's personal branding. This study uses a survey method involving 400 Generation Z respondents living in the Special Region of Yogyakarta. Data analysis techniques include validity and reliability tests, descriptive analysis, and hypothesis testing using correlation and simple linear regression. Meanwhile, to see the highest response from respondents, the Respondent Achievement Level (TCR) test is used. The results of the study show that Prabowo Subianto's personal branding has a positive and significant influence on Generation Z voters' interest. From the results of the coefficient of determination test, it was found that the influence of Prabowo Subianto's personal branding on the interest of Generation Z voters in DIY in the 2024 Presidential Election was 61%, the most influential factors in Prabowo's personal branding were aspects of leadership, personality, and good name.